Implementing a Dual Screening Protocol for Diabetes and Frailty in a Community-Dwelling Older Adults - Ardian, Laurentius Johan; Santoso, Aktaruddin Arief; Fahma, Hilmia; Gusyono, Anoraga Mona Cinta Gadis Cantika; Verbimanto, Satria Fudi (Unram Journal of Community Service, 2025)
Frailty, a significant geriatric syndrome, is a major complication of diabetes and is associated with adverse health outcomes. Indonesia, with its rapidly aging population, faces a substantial burden from these conditions. Community-based screening is essential for early detection and intervention. A community engagement program was conducted in Gunung Anyar District, Surabaya, involving 189 elderly participants. Simultaneous screenings for diabetes (via random blood glucose test) and frailty (using the validated FRAIL questionnaire) were performed. The study revealed a high dual burden of disease: 42.0% of participants had blood glucose levels indicative of diabetes, while 11.6% were classified as frail and 39.7% as pre-frail. About 30% of them were both unfit and poor glycemic control. This program demonstrates a high prevalence of diabetes and frailty among community-dwelling older adults in Surabaya, underscoring the urgent need for integrated geriatric care. The successful implementation of dual screening highlights the feasibility of incorporating these measures into primary care and the critical role of training community health workers to enable sustainable, early detection and management strategies.